2008
DOI: 10.1200/jco.2007.15.4336
|View full text |Cite
|
Sign up to set email alerts
|

Serum TIMP-1 and Response to the Aromatase Inhibitor Letrozole Versus Tamoxifen in Metastatic Breast Cancer

Abstract: Patients with elevated pretreatment serum TIMP-1 had a significantly reduced response and survival. Serum TIMP-1 was an independent predictive and prognostic factor. Blockade of TIMP-1 and HER-2/neu activity may be beneficial in a subset of patients with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…Interestingly, this association has also been demonstrated in metastatic colorectal cancer [23]. Furthermore, Lipton et al [13] showed that high serum TIMP-1 levels were predictive of low objective response rate of endocrine therapy in metastatic breast cancer. Recently, we have also shown that TIMP-1 immunoreactivity in breast cancer is associated with benefit from adjuvant anthracycline treatment but not from adjuvant treatment with CMF [15].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Interestingly, this association has also been demonstrated in metastatic colorectal cancer [23]. Furthermore, Lipton et al [13] showed that high serum TIMP-1 levels were predictive of low objective response rate of endocrine therapy in metastatic breast cancer. Recently, we have also shown that TIMP-1 immunoreactivity in breast cancer is associated with benefit from adjuvant anthracycline treatment but not from adjuvant treatment with CMF [15].…”
Section: Discussionmentioning
confidence: 84%
“…Tissue inhibitor of metalloproteinases-1 (TIMP-1) has proven to be a promising marker in breast cancer carrying both prognostic [7][8][9][10][11] and, as shown more recently, predictive information [12][13][14][15]. For example, our laboratory has previously demonstrated that high primary tumor tissue levels of TIMP-1 were significantly associated with a poor response to the most frequently used chemotherapeutic drugs in metastatic breast cancer [14].…”
Section: Introductionmentioning
confidence: 99%
“…The full network included 4 unique studies comparing tamoxifen (20 mg/day) to letrozole [31][32][33][34][35][36][37][38][39][40], anastrozole (TARGET [30,[41][42][43] and North American [29,44] studies), and exemestane [45][46][47][48][49][50][51][52]. One study comparing anastrozole to tamoxifen (40 mg/day) [53] was excluded because the dosage was incomparable to dosages of tamoxifen used in the other studies.…”
Section: Resultsmentioning
confidence: 99%
“…From a clinical point of view, it is therefore of particluar interest that low expression of TIMP1 in resected lung tumour tissue could be also an effective prognosis marker. However, other reports indicate that high TIMP1 levels in blood are associated with poor prognosis in some cancers 37,38 . A murine model of experimental liver metastasis suggests that the metastasis-mediated by TIMP1 may depend on the specific microenvironmental context 39 .…”
Section: Wt-timp1kd +Timp1mentioning
confidence: 98%